Screening of thyroid disorders in age and gender groups in a teaching hospital of Nowshera - Khan, Hamzullah; khan, Fawad; khan, Zahid; Ahmed, Naseer; khan, Waseemyar (Journal of Fatima Jinnah Medical University, 2021)
Background: In Pakistan 28.7% of the population had some degree of goiter. Out of those 40% of the nodules behaved hyperthyroidism based on the lower-than-normal values of thyroid stimulating hormones (TSH). Present study was designed as to determine the screening of thyroid disorders on the basis Thyroid Stimulating Hormone (TSH) in age and gender groups in a hospital-based study. Patients and methods: This cross-sectional study was conducted in Qazi Hussain Ahmed Medical Complex Nowshera from March 2019 to Jan 2020. Total 392 cases, 167 (42.6%) males and 225 (57.4%) females were included. All patients referred to pathology laboratory for measurement of TSH levels irrespective of age and gender were included to measure incidence of hyper, hypo or euthyroid status. Exclusion criteria were patients taking medications or iodine supplementation. Numerical variables like age and TSH values were presented with Mean with SD, Median and range. Inferential statistics and correlation statistics (chi-Square, ANOVA, Mann-Whitney U test and Spearman correlation) were used to determine the difference of TSH values in gender and age groups. Results: Mean age of the patients was 31+8.1 years. Mean TSH was 5.22+16.5 ng/ml. The difference of TSH values in the age categories using one way ANOVA statistics was insignificant (p = 0.15). Mann Whitney U Test confirmed that the distribution of TSH is the same across the categories of gender (p=0.001). Total 55 (14%) patients were hyperthyroid, and 23 (5.9%) mild hypothyroid and 30 (7.7%) hypothyroid. Chi square test showed the relation of gender with hypo and hyperthyroidism as statistically isignificant ( p= 0.18, p=0.8) respectively. Spearman ranked correlation test showed a mild to moderate inverse correlation of hypothyroidism with increase in age categories (p=0.88, r=-0.47) and a moderate uphill correlation of hyperthyroidism with increase in age categories, again statistically insignificant (p= 0.31, r=0.51). Conclusion: We observed a skewed distribution of TSH in our population. On the basis of the TSH values the thyroid disorders were categorized in hyper and hypothyroidism. There was a negative correlation of Hypothyroidsim (TSH<0.4) with age. While a positive correlation of age was noted with hyperthyroidism. While no significant relationship of hyper or hypothyroidism was noted in gender groups.